Pengaruh Progressive Muscle Relaxation (PMR) Terhadap Tekanan Darah Pada Pasien Hipertensi Di RS Grha Permata Ibu: The Effect of Progressive Muscle Relaxation (PMR) on Blood Pressure in Hypertensive Patients at Grha Permata Ibu Hospital - Asri Amanah Puspitasari; Yeni Koto; Susaldi (MPI Press, 2026)
Introduction: Hypertension is a health problem that occurs in every country worldwide. Management of hypertension patients includes two aspects: pharmacological therapy to reduce hypertension and prevent complications such as heart attacks. Pharmacological therapies that can be used include captopril, hydrochlorothiazide, methyldopa, metoprolol, and prasosin. Non-pharmacological therapies include deep breathing relaxation techniques, rose aromatherapy, steam bath therapy, foot reflexology, hypnotherapy, and progressive muscle relaxation. Objectives: To determine the effect of Progressive Muscle Relaxation (PMR) on blood pressure in hypertensive patients at Grha Permata Ibu Hospital. Method: The research design used in this study was a quasi-experimental one with a pretest-posttest approach. This approach involved a pretest, followed by treatment or intervention, and then a posttest to determine changes before and after the treatment or intervention. Result: The paired t-test showed a p-value of 0.001, meaning P <0.05. Therefore, it can be concluded that the administration of Progressive Muscle Relaxation and antihypertensive medication has an effect on Blood Pressure in hypertensive patients at Grha Permata Ibu Hospital. Conclusion: Progressive Muscle Relaxation has a positive impact on reducing blood pressure in hypertensive patients, so it is worth considering as a complementary therapy approach that can optimize hypertension management.